2018
DOI: 10.1029/2017gb005747
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of Ecosystem Scale Methane Emission From a Boreal Fen in Relation to Temperature, Water Table Position, and Carbon Dioxide Fluxes

Abstract: We have analyzed decade‐long methane flux data set from a boreal fen, Siikaneva, together with data on environmental parameters and carbon dioxide exchange. The methane flux showed seasonal cycle but no systematic diel cycle. The highest fluxes were observed in July–August with average value of 73 nmol m−2 s−1. Wintertime fluxes were small but positive, with January–March average of 6.7 nmol m−2 s−1. Daily average methane emission correlated best with peat temperatures at 20–35 cm depths. The second highest co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
109
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 73 publications
17
109
3
Order By: Relevance
“…Moreover, Korrensalo (2017) showed that biomass production rates on the same bog site are similar among the plant community types, except on bare peat surfaces that produce very little biomass. This can also partly explain our result, as methane emission has a positive correlation with primary production (Whiting and Chanton, 1993;Rinne et al, 2017).…”
supporting
confidence: 70%
“…Moreover, Korrensalo (2017) showed that biomass production rates on the same bog site are similar among the plant community types, except on bare peat surfaces that produce very little biomass. This can also partly explain our result, as methane emission has a positive correlation with primary production (Whiting and Chanton, 1993;Rinne et al, 2017).…”
supporting
confidence: 70%
“…Similar to chamber and EC measurements (Rinne et al, , 2018Jackowicz-Krczyński et al, 2010;Turetsky et al, 2014;Mikhaylov et al, 2015), direct ebullition studies have connected the rate of methane emission to peat temperature (Strack et al, 2005) related to increasing microbial activity (Conrad et al, 1997). It is noteworthy that the incoming energy flux has been shown to primarily control the methane production and ebullition in shallow subarctic lakes (Wik et al, 2014) that could be contrasted to peatland pools.…”
Section: Introductionmentioning
confidence: 80%
“…Alternatively, the eddy covariance (EC) technique is used to estimate the integrated ecosystem-scale methane flux (e.g. Brown et al, 2014;Rinne et al, 2018) but is unable to differentiate the emission pathways.…”
Section: Introductionmentioning
confidence: 99%
“…However, CH 4 emissions have less well understood hysteresis dynamics. Lagged emissions have been shown over the growing season with respect to water table depths (Moore & Roulet, ), gross primary productivity (Rinne et al, ), and annually with soil temperatures (Zona et al, ). At Ivotuk, a dry, upland tundra site similar to EML, strong seasonal hysteresis was attributed to stronger spring CH 4 oxidation, while later in the season more CH 4 is stored in the deeper active layer (Zona et al, ).…”
Section: Discussionmentioning
confidence: 99%